HAK MORAL PENCIPTA ATAS KARYA CIPTA YANG DIUNDUH DARI INTERNET - Theresia N. A. Narwadan (Faculty of Law, Universitas Pattimura, 2014)
This paper aimed to understand the factors inhibiting legal protection for the moral rights of the author from free internet downloading and causes for difficulties in punishing downloading from internet. Eventhough Indonesia has the copyright’s act since 1912, but until today the infringement of copyrights be on increase. People can get all they need which they want to hear or they want to read from internet downloading. For example, Asosiasi Industri Rekaman Indonesia (ASIRI) shown that the authors lose a lot of money because of free internet downloading. According to Asosiasi Rekaman Indonesia-ASIRI’s estimate that Indonesia was lose Rp 762.000.000.000,- a year because of free internet downloading. The factors inhibiting legal protection, for the moral rights of the authors from free internet downloading include the authors’ lack of understanding on their own moral rights, and the lack of appreciation in free internet downloading. The dispute resolution faces difficulties in deciding the punishment, for free downloading from internet, since the police have no accurate understanding on the Act No 28/2014 about Copyrights. In addition, the creators must be more active to file their complaints, despite the fact that the infringement of moral copyrights is categorized as ordinary delict in the Act No 28/2014, whenever they find out that their creation are offered for free download without their written permission. The author must play more active role as they are supposed to know better the originality of their creation.